Unraveling Heart Inflammation: Recurrent Myopericarditis Caused by Coxsackie A Virus—A Case Report - Maisha Maliha; Vikyath Satish; Kuan Yu Chi; Nishat Shama; Sananda Halder; Sumaiya Monjur Oishy; Amrin Kharawala; Dimitrios Varrias; Robert T. Fallaice (Clinical Case Reports)
ABSTRACT Acute recurrent myopericarditis, characterized by the occurrence of a new myopericarditis event following a symptom‐free interval of 4–6 weeks, is relatively rare lacking definitive guidelines for management. Understanding its prevalence, causes, and optimal management is challenging due to limited data and insufficient guidelines. This case outlines the diagnostic work‐up and different management modalities for recurrent myopericarditis. A 44‐year‐old African American man with a past medical history of myopericarditis a year ago presented with fever and chest pain for 4 days. The patient was found to have elevated troponin, CRP, and ESR; pericardial effusion along with a Coxsackie A virus titer of 1:800, suggestive of Coxsackie A virus–induced recurrent myopericarditis. The patient responded well to colchicine and a tapering dose of ibuprofen, achieving significant resolution in the pericardial effusion. Recurrent myopericarditis caused by Coxsackie A virus is a relatively rare phenomenon. New onset myopericarditis can be caused by various factors such as infections, autoimmune disorders, neoplasms, metabolic issues, trauma, and drugs, with recurrence rates of 15%–50% in pericarditis patients. Coxsackie A virus is an important and rare etiology of recurrent myopericarditis due to its unique immune evasive traits. The treatment modalities guided by definitive guidelines for recurrent pericarditis can be applied in recurrent myopericarditis with significant resolution of symptoms. Although there are no specific guidelines for managing recurrent myopericarditis, using approaches designed for recurrent pericarditis has shown promising results, and the immune evasive nature of Coxsackie A virus underscores the need for further research to improve our understanding and treatment of this condition.